Resonant doping for high mobility transparent conductors: the case of Mo-doped In2O3. Issue 1 (17th September 2019) - Swallow, Jack E. N.; Williamson, Benjamin A. D.; Sathasivam, Sanjayan; Birkett, Max; Featherstone, Thomas J.; Murgatroyd, Philip A. E.; Edwards, Holly J.; Lebens-Higgins, Zachary W.; Duncan, David A.; Farnworth, Mark; Warren, Paul; Peng, Nianhua; et al.
Abstract : Superior transparent conducting properties of indium oxide realised by molybdenum donors resonant in the conduction band, avoiding detrimental effects of tin doping. Abstract : Transparent conductors are a vital component of smartphones, touch-enabled displays, low emissivity windows and thin film photovoltaics. Tin-doped In2 O3 (ITO) dominates the transparent conductive films market, accounting for the majority of the current multi-billion dollar annual global sales. Due to the high cost of indium, however, alternatives to ITO have been sought but have inferior properties. Here we demonstrate that molybdenum-doped In2 O3 (IMO) has higher mobility and therefore higher conductivity than ITO with the same carrier density. This also results in IMO having increased infrared transparency compared to ITO of the same conductivity. These properties enable current performance to be achieved using thinner films, reducing the amount of indium required and raw material costs by half. The enhanced doping behavior arises from Mo 4d donor states being resonant high in the conduction band and negligibly perturbing the host conduction band minimum, in contrast to the adverse perturbation caused by Sn 5s dopant states. This new understanding will enable better and cheaper TCOs based on both In2 O3 and other metal oxides.